4.9% Au stabilizes Ag in an atomically homogenous bimetallic alloy for anisotropic nanocrystals with enhanced stability under light irradiation. Issue 23 (7th June 2021) - Xu, Zhenying; Xie, Hao; Ye, Weixiang; Yang, Yi; Ni, Weihai
Abstract : Atomically homogenous AuAg alloy nanocrystals with Au fraction as low as 4.9% (at%) possesses a comparable stability to Au, while the superior plasmonic properties of Ag are largely reserved. Abstract : Instability problems encountered by Ag nanocrystals largely limit their use in practical applications. In AuAg bimetallic alloys, the stability of Ag can be greatly enhanced, whereas doping a high fraction of Au to the alloy usually leads to the loss of the superior properties of Ag and undesirable degradation of the quality factor of the plasmonic resonance. Herein, we provide experimental evidence that the atomically homogenous AuAg alloy nanocrystals with Au fraction as low as 4.9% (at%) possess comparable stability to pure Au, while the superior plasmonic properties of Ag are largely reserved. The study is based on the synthetic strategy developed for the overgrowth on the Au nanorods of atomically homogenous AuAg alloy shells with a tunable Au/Ag ratio but constant size and anisotropic shape. The stability of over 800 individual alloy nanocrystals in the absence of surfactants is simultaneously characterized at the single-particle level for over 10 h under light irradiation. The stability transition is explained in correlation with the charge redistribution of Ag occurring at the same critical Au fraction. We note that such bimetallic alloy nanocrystals with a low Au fraction possessing both high stability and high quality of resonance are preferred in fundamental researches and practical applications.